2017
DOI: 10.1007/s41686-017-0007-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Student Perceptions of the Use of Open Educational Resources to Reduce Statistics Anxiety

Abstract: Numerous instructional strategies have been applied to minimize statistics anxiety. Instructors are likely to consider those strategies a burden and may hesitate to apply them in their courses if there is a lack of continuous support. Open educational resources (OERs) enabled by information and communication technology have the potential to resolve this concern owing to their cost-effectiveness and to the prolific collections available. OERs can be adopted through reuse, redistribution, revision, and remix. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Open educational resources OER are openly licensed educational materials that allow users to retain, reuse, revise, remix and redistribute them at no costs (Hilton, 2016;Lin & Tang, 2017). That is, users can download and keep a copy of OER (revise); utilize OER or a portion of OER (reuse); make changes to ("revise") or merge ("remix") any existing OER; and share and disseminate OER with limited restrictions (redistribute), complying with the licenses established by CC (Lin & Tang, 2017). For example, the CC-BY license allows users to adapt and share OER for commercial or noncommercial purposes, while the CC-BY-NC only authorizes users to do so for noncommercial purposes (Hilton, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Open educational resources OER are openly licensed educational materials that allow users to retain, reuse, revise, remix and redistribute them at no costs (Hilton, 2016;Lin & Tang, 2017). That is, users can download and keep a copy of OER (revise); utilize OER or a portion of OER (reuse); make changes to ("revise") or merge ("remix") any existing OER; and share and disseminate OER with limited restrictions (redistribute), complying with the licenses established by CC (Lin & Tang, 2017). For example, the CC-BY license allows users to adapt and share OER for commercial or noncommercial purposes, while the CC-BY-NC only authorizes users to do so for noncommercial purposes (Hilton, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared with traditional textbooks, open licensed textbooks are more likely to fulfill teachers' needs to provide differentiated instruction (Blomgren, 2018). In addition, research has indicated that classes that implement OER show no harm to course outcome and student motivation when they are compared to classes that use traditional textbooks (Lin & Tang, 2017;Tang & Bao, 2020). Therefore, advocating that K-12 teachers implement OER has become necessary for personalized instruction in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…OER provide users with free access to openly licensed educational materials that users may utilize, manipulate, and share for their own purposes (UNESCO 2002). With users granted the permission to retain, reuse, revise, remix, and redistribute these resources, OER allow educators to customize and reproduce a broad collection of materials (Hilton 2016;Hilton et al 2010;Lin & Tang 2017). They also have obvious positive financial implications, but without any deterioration of pedagogical value: evidence that OER can decrease students' educational costs without harm to their course performance has been well documented.…”
Section: Open Educational Resourcesmentioning
confidence: 99%